2022
DOI: 10.3389/fneur.2022.999375
|View full text |Cite
|
Sign up to set email alerts
|

Brain morphology changes after spinal cord injury: A voxel-based meta-analysis

Abstract: ObjectivesSpinal cord injury (SCI) remodels the brain structure and alters brain function. To identify specific changes in brain gray matter volume (GMV) and white matter volume (WMV) following SCI, we conducted a voxel-based meta-analysis of whole-brain voxel-based morphometry (VBM) studies.MethodsWe performed a comprehensive literature search on VBM studies that compared SCI patients and healthy controls in PubMed, Web of Science and the China National Knowledge Infrastructure from 1980 to April 2022. Then, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 82 publications
1
5
0
Order By: Relevance
“… 66 Our hypothesis is further supported by the evidence base in SCI, where a meta-analysis of MRI brain activation in traumatic SCI similarly concluded that brain changes were likely a function of direct loss of function (comparable to our ‘pathological changes’ hypothesis) and adaptive cortical reorganization (comparable to our ‘compensatory changes’ hypothesis). 67 Moreover, a more recent voxel-based meta-analysis of structural MRI changes proposed that significant insular atrophy following SCI may in part contribute to the subsequent depression reported in patients, 68 providing additional support for our hypothesis that ‘pathological changes’ beyond the spinal cord occur and may help to explain the occurrence of symptoms in DCM.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“… 66 Our hypothesis is further supported by the evidence base in SCI, where a meta-analysis of MRI brain activation in traumatic SCI similarly concluded that brain changes were likely a function of direct loss of function (comparable to our ‘pathological changes’ hypothesis) and adaptive cortical reorganization (comparable to our ‘compensatory changes’ hypothesis). 67 Moreover, a more recent voxel-based meta-analysis of structural MRI changes proposed that significant insular atrophy following SCI may in part contribute to the subsequent depression reported in patients, 68 providing additional support for our hypothesis that ‘pathological changes’ beyond the spinal cord occur and may help to explain the occurrence of symptoms in DCM.…”
Section: Discussionsupporting
confidence: 63%
“…Finally, it is important to acknowledge that our proposed distinction of ‘pathological’ and ‘compensatory’ brain changes in DCM remains a hypothesis at this stage, although the evidence for brain changes in related fields, such as SCI, is now well-established. 67 , 68 We believe that this working hypothesis provides a useful direction for the field as distinguishing between brain changes related directly to spinal cord injury from those as a result of adaptation may have differing implications for prognostication and guiding the development of novel therapies (e.g., regenerative strategies for ‘pathological changes’ versus plasticity-enhancing therapies for ‘compensatory changes’). Importantly, more evidence in the form of preclinical studies and MRI studies in vivo are now required to confirm (or refute) our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…12 According to a voxel-based meta-analysis published in 2022, multiple studies have shown consistent gray matter volume reduction in bilateral insula post-SCI. 13 Additionally, stronger FC between the insula and thalamic subregions was noted in those with greater intensities of NP. This indicates that alterations in gray matter volume are likely due to a consequence of NP post-SCI rather than trauma from SCI.…”
Section: Discussionmentioning
confidence: 96%
“…As the disruption of local brain networks is unique to each subtype of chronic pain, accumulating data on local brain regions such as the insula can help understand specific disease alterations 12 . According to a voxel‐based meta‐analysis published in 2022, multiple studies have shown consistent gray matter volume reduction in bilateral insula post‐SCI 13 . Additionally, stronger FC between the insula and thalamic subregions was noted in those with greater intensities of NP.…”
Section: Discussionmentioning
confidence: 99%
“…19 The thalamus is an important relay station which receives sensory and motor information, then processes the signals and transmits it to the cerebral cortex. 20 The MCC selectively mediate the concordance of sensorimotor information and self-initiated movements. 21 In addition, previous studies have suggested that cerebellar lobules IV-VI are located in the cerebello-thalamo-motor cortical pathway and principally engaged in motor control and somatosensory functions.…”
Section: Alteration Of Sensory Motor Related Brain Regionsmentioning
confidence: 99%